Understanding rural caregivers' experiences of cancer care when accessing metropolitan cancer services: a qualitative study. Issue 7 (11th July 2019) - Ugalde, Anna; Blaschke, Sarah; Boltong, Anna; Schofield, Penelope; Aranda, Sanchia; Phipps-Nelson, Jo; Chambers, Suzanne K; Krishnasamy, Meinir; Livingston, Patricia M
Abstract : Objective: To explore the experiences of cancer caregivers who live in rural Australia and travel to a metropolitan cancer health service to access cancer treatment. Design: A qualitative study using semistructured, audio-recorded interviews conducted between December 2017 and July 2018 with caregivers and social workers. Thematic analysis using interpretative descriptive techniques performed on textual interview data within a critical realist paradigm to develop understanding of rural caregivers' lived experiences. Setting: Participants were from rural areas attending a metropolitan cancer centre in Australia and social workers. Participants: 21 caregivers (16 female) of people with cancer living in rural Australia within a minimum distance of 100 km from the metropolitan cancer centre where they access treatment, and five social workers employed at a metropolitan cancer service with experience of working with rural patients and caregivers. Results: Thematic analysis developed two overarching themes: theme 1: caregiving in the rural setting describes the unique circumstance in which caregiving for a person with cancer takes place in the rural setting at considerable distance from the cancer service where the person receives treatment. This is explored in three categories: 'Rural community and culture', 'Life adjustments' and 'Available supports'. Theme 2: accessing metropolitan cancer services captures the multiplicity of tasks and challenges involved in organising and coordinating the journey to access cancer treatment in a metropolitan hospital, which is presented in the following categories: 'Travel', 'Accommodation' and 'Health system navigation'. Conclusions: Caregivers who live in rural areas face significant challenges when confronting geographic isolation between their rural home environment and the metropolitan setting, where the patient accessed cancer treatment. There is a need for healthcare services to identify this group to develop feasible and sustainable ways to provide interventions that have the best chance of assisting rural caregivers in supporting the patient while maintaining their own health and well-being.